Diskriminasi Terhadap Buruh Tani Perempuan di Jorong Koto Baru Nagari Koto Baru, Kabupaten Solok - Aminah, Maiza; Bakhtiar, Yusnanik; Muchtar, Henni (Journal of Civic Education, 2024)
This study explores the forms, causes, and impacts of discrimination faced by female farm laborers in Jorong Koto Baru, Nagari Aie Dingin, Solok Regency. Employing a qualitative approach with a case study design, the research involved informants such as the village head (jorong), landowners, female and male farm laborers, and the families of farm workers. Data were collected from primary and secondary sources through observations, interviews, and documentation. To ensure validity, source triangulation was applied. The data analysis process included reduction, presentation, and conclusion drawing. The findings reveal three main forms of discrimination experienced by female farm laborers: wage disparities, unequal treatment, and the burden of dual workloads. These discriminatory practices are rooted in patriarchal societal norms that perceive women as subordinate. The impacts of this discrimination include significant debt due to inadequate wages, limited social interaction with the community caused by exhaustive daily work schedules, deteriorating physical health due to insufficient rest, and strained family relationships resulting from a lack of communication.